2010
DOI: 10.1038/sc.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb reconstructive surgery uptake for persons with tetraplegia in New Zealand: a retrospective case review 2001–2005

Abstract: Study design: Retrospective case series. Objective: To describe the uptake of upper limb surgery by individuals with tetraplegia in New Zealand (NZ). Setting: New Zealand. Methods:The clinical notes of all individuals who sustained a cervical spinal cord injury between 1 January 2001 and 31 December 2005 were retrospectively reviewed for those who met the clinical criteria to undergo upper limb surgery. Cases were cross-referenced to the hand surgery record to determine the uptake of upper limb surgery in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Individuals with tetraplegia need to be referred to these services to be fully informed about their options, and the service needs to be accessible/flexible to meet their needs. Significant differences in access and equity to such services are apparent within the literature for UE surgery for tetraplegia, where in the United States, only 7% of eligible people with tetraplegia have UE reconstructive procedures [ 42 , 43 , 44 ] compared to Aotearoa/New Zealand, with the uptake closer to half the eligible population [ 45 ]. However, urgent investigation is required given previously reported differences for surgery uptake for Māori in this cohort [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with tetraplegia need to be referred to these services to be fully informed about their options, and the service needs to be accessible/flexible to meet their needs. Significant differences in access and equity to such services are apparent within the literature for UE surgery for tetraplegia, where in the United States, only 7% of eligible people with tetraplegia have UE reconstructive procedures [ 42 , 43 , 44 ] compared to Aotearoa/New Zealand, with the uptake closer to half the eligible population [ 45 ]. However, urgent investigation is required given previously reported differences for surgery uptake for Māori in this cohort [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 A previous NZ study found that the uptake of reconstructive UL surgery was close to half (44%) the eligible population. 6 Uptake in the New Zealand is substantively higher than the reported uptake in the United States, [7][8][9] although in the New Zealand, women and those who identified as NZ Maori were underrepresented in the surgery group. 6 Low uptake of reconstructive UL surgery is an important issue worldwide.…”
Section: Introductionmentioning
confidence: 85%
“…6 Uptake in the New Zealand is substantively higher than the reported uptake in the United States, [7][8][9] although in the New Zealand, women and those who identified as NZ Maori were underrepresented in the surgery group. 6 Low uptake of reconstructive UL surgery is an important issue worldwide. One of the most commonly cited reasons for low utilisation in the United States is the lack of clarity in the existing literature about the value of the procedures performed 5,[8][9][10][11] This makes it difficult for physicians and health professionals to summarise useful information from the literature for patients and even more difficult for people with tetraplegia to find this information for themselves.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation